Niveles de arsénico y flúor en agua de bebida animal en establecimientos de producción lechera (Pcia. de Córdoba, Argentina) - Pérez Carrera, A. (2004)
Southeastern Cordoba (Argentina) is one of the regions in the country more affected by high arsenic groundwaters. Poor water quality may influence the development of agricultural activities in spite of the favorable edaphic and climatic characteristics. Water quality for dairy cattle was evaluated in 32 dairy farms (Long. 62º 33´ W and 62º 57´ W; and Lat. 32º 12´S and 32º 50´ S) that use groundwater as the main source. Wells take water from different depth (3 - 15 m, 40% and 80 - 150 m, 44%). Mayor ion concentrations are within the recommended values in water for dairy cattle. Arsenic and fluoride contents are higher in shallow groundwater where a 52.6% and a 84.2% of the samples, respectively, show higher concentrations than those recommended for dairy cattle, while only 5.6% of samples from deeper perforations were above the suggested limits for both elements.